Teaching Knowledge Synthesis Methods through Online Research Consultations: A Story of Invisible Labour - Parker, Robin M. N.; Snelgrove-Clarke, Erna (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
Requests to meet with academic librarians for support on knowledge synthesis (KS) projects have escalated due to an increasing number of learners embarking on KS projects as part of their course work, along with the recommendation in KS methods guidance to consult with a research librarian to ensure a comprehensive search. While there are program descriptions and evaluations of library-led and other KS methods training for groups or self-directed learning opportunities, little evidence examines the teaching practices of academic librarians in individual KS research consultations. The objective of this research is to explore teaching encounters during online KS research consultations and describe the often invisible aspects of that labour through the findings from an online-mediated, focussed ethnographic study. The study draws on data from focus groups, observations and interviews, as well as autoethnographic sources. We use a sociomaterial lens to analyze the stories in the data and illuminate the complexities of the virtual, synchronous teaching encounter between academic health librarians and learners. We present a composite narrative elaborating on the social, technical, and material elements assembled before, during, and after an online KS methods consultation to emphasize the invisible and affective labour of librarian teaching practices about comprehensive searching and KS methods.